Psychological elements in modern poems “Bintang Hati” - Mashor Awang Long; Asmiaty Amat; Sim Chee Cheang; Sharifuddin Zainal; Amsalib Pisali; Yani Maemunah (e-International Publishing House, 2025)
This research paper discusses the psychological elements found in modern KOMSAS poetry. This study employs a qualitative method, specifically text analysis. Four modern poems from the Bintang Hati anthology are the focus of this study, namely: (1) Kijang yang Lelah, (2) Pesan Ibu Beribu-ribu, (3) Senja di Palang Besi, and (4) Bintang. This research applies Maslow’s psychological theory of human needs, which encompasses aspects such as physiological needs, safety, love, self-esteem, and self-actualization. The findings of this study indicate that psychological elements in KOMSAS poems significantly help readers gain a deeper understanding of the meaning the author intends to convey.